The role of a best practice alert in the electronic medical record in reducing repetitive lab tests - Bejjanki H; Mramba LK; Beal SG; Radhakrishnan N; Bishnoi R; Shah C; Agrawal N; Harris N; Leverence R; Rand K (Dove Medical Press, 2018)
Harini Bejjanki,1 Lazarus K Mramba,2 Stacy G Beal,3 Nila Radhakrishnan,1 Rohit Bishnoi,1 Chintan Shah,1 Nikhil Agrawal,4 Neil Harris,3 Robert Leverence,1 Kenneth Rand3 1Division of Hospital Medicine, Department of Medicine, University of Florida, Gainesville, FL, USA; 2Statistics, Department of Internal Medicine, University of Florida, Gainesville, FL, USA; 3Department of Pathology, Immunology, & Laboratory Medicine, College of Medicine, University of Florida, Gainesville, FL, USA; 4Department of Nephrology, Beth Israel Deaconess Medical Center, Harvard Medical School, Boston, MA, USA Background: The recommendations of the American Board of Internal Medicine Foundation’s “Choosing Wisely®” initiative recognize the importance of improving the appropriateness of testing behavior and reducing the number of duplicate laboratory tests.Objective: To assess the effectiveness of an electronic medical record Best Practice Alert (BPA or “pop up”) intervention aimed at reducing duplicate laboratory tests and hospital costs.Design: Comparison of the number of duplicated laboratory tests performed on inpatients before and after the intervention.Setting: University of Florida Health Shands Hospital, Gainesville, FL, USA, during 2014–2017.Intervention: The electronic medical record intervention was a BPA pop-up alert that informed the ordering physician if a recent identical order already existed along with the “ordering time”, “collecting time”, “resulting time”, and the result itself.Main outcome measures: Percentage change in the number of inpatient duplicate orders of selected clinical biochemistry tests and cost savings from reduction of the duplicates. Student’s t-test and beta-binomial models were used to analyze the data.Results: Results from the beta-binomial model indicated that the intervention reduced the overall duplicates by 18% (OR=0.82, standard error=0.016, P-value<0.000). Percent reductions in 9 of the 17 tests were statistically significant: serum hemoglobin A1C level, vitamin B12, serum erythrocyte sedimentation rate, serum folate, serum iron, lipid panel, respiratory viral panel, serum thyroid stimulating hormone level, and Vitamin D. Additionally, important cost savings were realized from the reduction of duplicates for each lab test (with the exception of CRP) with an estimated overall savings of $72,543 over 17 months in the post-intervention period.Conclusions: The present study included all hospital inpatients and covered 17 clinical laboratory tests. This rather simple and low-cost intervention resulted in significant reductions in percentage duplicates of several tests and resulted in cost savings. The study also highlights the role of hospitalists in quality improvement. Keywords: laboratory, testing, health care, costs